THE EFFECT OF THE INTEGRITY AND TIME PRESSURE AUDITOR ON TAX AUDIT QUALITY (Survei On West Java I Regional Tax Office I) - Nenden Susilawati (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
This study aims to examine the effect of auditor integrity and time pressure on the quality of tax audits. The research wasconducted in the Regional Office of the DJP-West Java I located in the area of ​​West Java I. The research population involved all functional tax audit officers in the Regional Office of the Directorate General of Taxes -West Java I. The sampling technique used probability sampling. The research sample consisted of 114 respondents consisting of Supervisors, Team Heads, and examiner functional members. The results of this study indicate that the integrity variable and the examiner's time pressure variable have a positive effect on the quality of tax audits. Theoretically, the research results can provide a reference for future research so that further research can expand its research by adding research variables other than the variables carried out in this study, besides that it can be used as evaluation material for related institutions, namely the Directorate General of Taxes in particular and generally for work units in the Indonesian Ministry of Finance Region, namely all examiner functions at the Directorate General of Taxes in an effort to improve the quality of tax audits.